Study on the Expressive Characteristics of Interactive Fashion Art - Gao Rusi (International Journal of Advanced Culture Technology(IJACT), 2025)
This study explores the expressive characteristics of interactive fashion art by examining its conceptual, material, and experiential dimensions. Building upon a theoretical framework combining fashion art and interactive art, the research analyzes five representative international artworks created from the late 20th century to the present. Through empirical analysis, it identifies objectivity, interactivity, and complexity as the most highly correlated expressive features, followed by conceptuality, creativity, and immersion. The findings highlight how interactive fashion art engages audiences through tactile participation, transforming passive spectatorship into active, personalized artistic experiences. Despite strong performance in interactivity and material engagement, the study notes limitations in media diversity and site-specificity, suggesting areas for future innovation through digital technologies. We are offering a systematic approach to evaluating interactive fashion art, thereby contributing to academic discourse and laying a theoretical foundation for future artistic and scholarly exploration.